2016
DOI: 10.1016/j.jctube.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy in persons with tuberculosis

Abstract: Peripheral neuropathy (PN) is a serious condition affecting the nerves that is commonly seen in patients with tuberculosis (TB). Causes of PN in patients with TB are multiple, and can include TB itself, other co-morbid conditions, such as Human Immune-deficiency virus (HIV) disease, malnutrition, or diabetes mellitus (DM), and several anti-tuberculous medications. The condition can manifest with a variety of symptoms, and a diagnosis can usually be made on a clinical basis. Treatment and prognosis of PN vary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…Tuberculosis (TB) remains a major public health concern in SEA, contributing to 40% of the global burden of disease, and the increasing incidence of HIV increases the risk of TB. TB is associated with PN, and antituberculous drugs, especially isoniazid, can lead to PN 5 . In addition, with drug‐resistant TB, various second‐line treatments, such as cycloserine, ethionamide, fluoroquinolones and newer drugs (such as linezolid), can cause PN (26%) 6 .…”
Section: Peripheral Neuropathy In Seamentioning
confidence: 99%
“…Tuberculosis (TB) remains a major public health concern in SEA, contributing to 40% of the global burden of disease, and the increasing incidence of HIV increases the risk of TB. TB is associated with PN, and antituberculous drugs, especially isoniazid, can lead to PN 5 . In addition, with drug‐resistant TB, various second‐line treatments, such as cycloserine, ethionamide, fluoroquinolones and newer drugs (such as linezolid), can cause PN (26%) 6 .…”
Section: Peripheral Neuropathy In Seamentioning
confidence: 99%
“…HIV infection itself results in an increased rate of serious adverse events in patients on TB treatment and ART may further increase this. 16 A retrospective cohart study in south Africa patients on rifampicin based TB treatment found increased serious adverse effects, primarily peripheral neuropathy and increased vomiting, in HIV infected compared with uninfected patients. 17 The same result was found in study of HIV associated sensory neuropathy probably because of combined toxicity of both drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known to cause various extra-pulmonary manifestations and can affect any part of the body, one such rarer manifestation that has been associated with it is peripheral neuropathy. How it affects the peripheral nerves has not been studied in great detail; various mechanisms have been linked to this including direct invasion, immune-mediated phenomenon, vasa vasorum inflammation, and effect of anti-TB medications, but due to the rarity of this condition limited work has been done on this topic [ 2 - 3 ].…”
Section: Introductionmentioning
confidence: 99%